Salivary oxytocin and touch in everyday life: Results from an EMA study during Covid-19 lockdown. (September 2021) - Schneider, E.; Hopf, D.; Eckstein, M.; Aguilar-Raab, C.; Scheele, D.; Hurlemann, R.; Ditzen, B.
Abstract : Background: Affectionate touch is important in human social life. Previous research demonstrated that touch is associated with release of endogenous oxytocin and has calming and stress reducing effects. Less is known about the impact of Covid-19-related lockdown on psychobiological outcomes in everyday life. We, thus, focused on the relationship between daily social touch and oxytocin levels during Covid-19 lockdown. Methods: 173 women and 74 men (age: M=32.6, SD=13.1) participated in ecological momentary assessment on two consecutive days during Covid-19 pandemic in Spring 2020. At 6 timepoints per day participants collected saliva samples and simultaneously reported subjective momentary burden, mood and social interactions, including social touch. Concentrations of salivary oxytocin, cortisol, and alpha amylase were analyzed using enzyme linked immunoassay. Results: Hierarchical linear model (HLM) analyzes showed a significantly negative association between social touch intensity and self-reported burden levels (t=-2.683; p=.007) as well as positive association with oxytocin concentrations (t=2.476; p=.013). Conclusions: These preliminary finding show that individuals experiencing intense social touch have higher salivary oxytocin concentrations and report less burden in their everyday life. While further analyses within this study are being conducted, these results suggest that oxytocin might play a mediating role between social touch and the individual's well-being.